Assistência técnica e extensao rural cooperativa: o perfil e o trabalho dos agentes de campo em uma cooperativa agropecuária em Minas Gerais, Brasil - Petarly, Renata Rauta (2017)
The objective of this paper is to describe how the Rural Extension and Technical Assistance performed by an agricultural cooperative and what is the profile of professionals responsible for it, wondering how she contributes in the associative and business aspects of cooperative management . The research was exploratory and descriptive, held in a cooperative of Minas Gerais. Interviews were conducted with all the cooperative field agents. It was evident that the agents fit into the context of technical and productive improvements, while contributing to the communication and representative process with cooperative education activities that promote social and economic participation of members